The Effect Of E-Services On Customer Commitments Medied By The Trust Variable - Nurcaya, I Nyoman (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 2 Tahun 2021DO - 10.24843/MATRIK:JMBK.2021.v15.i02.p10, 2021)
Customer commitment is one measure of the success of a company engaged in finance. Good service quality will increase customer commitment. Customers who have a high commitment will continue to carry out their financial transactions and inform others about the trust they get. This study aims to determine the impact of automated services (e-services) on customer commitment mediated by customer trust. This research was conducted at the Bali Regional Development Bank located in Denpasar – Bali. The sampling technique used is purposive sampling with a total sample of 90 customers. The data analysis technique used is Partial Least Square (PLS). The results of the analysis show that e-services have a significant positive effect on customer trust and customer loyalty. Customer trust has a significant positive effect on customer loyalty. Customer trust significantly mediates the effect of e-service on customer commitment.